Evaluation of Functional Selectivity of Haloperidol, Clozapine, and LASSBio-579, an Experimental Compound With Antipsychotic-Like Actions in Rodents, at G Protein and Arrestin Signaling Downstream of the Dopamine D2 Receptor - Silva, Rafaela R.; Parreiras-e-Silva, Lucas T.; Pompeu, Thais E.T.; Duarte, Diego A.; Fraga, Carlos A.M.; Barreiro, Eliezer J.; Menegatti, Ricardo; Costa-Neto, Claudio M.; Noël, François (Frontiers in Pharmacology, 2019)
LASSBio-579, an N-phenylpiperazine antipsychotic lead compound, has been previously reported as a D2 receptor (D2R) ligand with antipsychotic-like activities in rodent models of schizophrenia. In order to better understand the molecular mechanism of action of LASSBio-579 and of its main metabolite, LQFM 037, we decided to address the hypothesis of functional selectivity at the D2R. HEK-293T cells transiently co-expressing the human D2-LR and bioluminescence resonance energy transfer (BRET)-based biosensors were used. The antagonist activity was evaluated using different concentrations of the compounds in the presence of a sub-maximal concentration of dopamine (DA), after 5 and 20 min. For both signaling pathways, haloperidol, clozapine, and our compounds, act as DA antagonists in a concentration-dependent manner, with haloperidol being from far the most potent, consistent with its nanomolar D2R affinity measured in binding assays. In our experimental conditions, only haloperidol presented a robust functional selectivity being 4-5 fold more efficient for inhibiting translocation of β-arrestin-2 (β-arr2) than for antagonizing Gi activation. Present data are the first report on the effects of LASSBio-579 and LQFM 037 on β-arr2 signaling pathway and further illustrate that the functional activity could vary depending on the assay conditions and approaches used.